The Relationship Between Body Mass Index and Menstrual Cycle in Midwifery Students at dr. Soebandi University in Jember - ernawati anggraeni (LPPM Universitas dr. Soebandi, 2023)
According to WHO data there are 75% of women with menstrual disorders. About 60-70% of women with less and more weight (obesity) can show symptoms of menstrual cycle disorders. The purpose of this study was to determine the relation BMI with menstrual cycles midwifery students of Universitas dr. Soebandi in the Jember. Methods: This research design used Cross Sectional study design. The population in the study were midwifery students at the University of dr. Soebandi in Jember class of 2019-2021 amounted to 164 respondents with total sampling techniques as data collecting. The data collection using height and weight as measurements and questionnaires. Results: Most of the respondents had a normal body mass index (59.1%). Most respondents had normal menstrual cycles (62.8%). The results showed that most respondents (≥50%) with abnormal BMI categories experienced menstrual cycle disorders. Analysis: Univariate and bivariate data analysis using Spearman's Rank. Based on the results of statistical tests, there is a relationship between body mass index and menstrual cycle with a value of p = 0.01 and r = 0.470. Discuss: Students with abnormal body mass index potentially experience menstrual cycle disorders than the other with normal body mass index